The Relationship Between Physical Activity and Nutritional Status Based on Body Mass Index for Age Percentiles in Elementary School Children in Ciherang Village - Susy Olivia Lontoh; Yohanes Firmansyah; Ernawati Ernawati; Santoso, Alexander Halim; William Gilbert Satyanegara; Bryan Anna Wijaya; Fiona Valencia Setiawan; Nicholas Setia; Daniel Goh (HM Publisher, 2024)
Physical activity is crucial for children, and it is also useful in the prevention of obesity. In today's modern lifestyle, children are becoming more inactive, which puts them at risk of being overweight and obese. Studies have shown that physical activity and dietary changes can help reduce weight in obese children. Therefore, researchers are interested in studying the relationship between physical activity and nutritional status in children. This cross-sectional study was conducted in February-March 2024 at 5 Ciherang Elementary Schools. Children who meet the inclusion criteria will be asked questions about physical activity using the IPAQ questionnaire, followed by a measurement of body weight and height, and then nutritional status will be interpreted using the BMI per age chart from CDC. Two hundred forty-six children met the inclusion criteria, and it was found that there was no significant difference in the mean value of IPAQ between nutritional status groups based on BMI/Age (p-value = 0.844). In this study, it was found that there was no significant difference between physical activity duration and nutritional status in children.